African Theologies of Identity and Community: The Contributions of John Mbiti, Jesse Mugambi, Vincent Mulago, and Kwame Bediako - Tarus, David (Open theology, 2017)
This article examines four theologies of identity and community from Africa and their relevance in combating ethnocentrism in Africa. The article focuses on the works of Vincent Mulago, John S. Mbiti, Kwame Bediako, and J. N. K. Mugambi - the key proponents of the schools of thought that we examine. The themes of identity and community have practical implications. For example, a people’s perception of themselves and their communities (social identity) affects how they perceive and relate to others. Therefore, considering the challenge of ethnocentrism worldwide, the themes of identity and community must always be examined. This article has two major sections. Foremost, it explores the relationship of these concepts. Second, it examines and critiques African theologies of identity and community and their consequent theological implications for social cohesion of communities. Finally, it proposes a way forward utilizing contributions from each theologian.